E-tutors’ experiences with integrating technologies in online course modules: A case of open distance e-learning - Sedio, Mpipo Zipporah (Edelweiss Applied Science and Technology, 2024)
This study aims to explore how e-tutors’ experiences influence their ability to integrate technologies, with a focus on the realities of technology knowledge during the facilitation of modules in an Open Distance e-Learning (ODeL) context. A survey was conducted to investigate the experiences of e-tutors in integrating technology across various modules within a department of an ODeL institution. Six e-tutors participated in the survey, and their involvement was voluntary, with no impact on their employment contracts, ensuring informed participation. The research utilized the constructivist learning theory to examine how e-tutors prioritize student engagement and promote active involvement in technology-enhanced constructivist learning environments. Data collected were organized and displayed in tables. The findings revealed that e-tutors had positive experiences integrating technologies into online module teaching. Additionally, they recognized the role of technology in supporting and enhancing the teaching of online student activities. These results provide further insight into the use of technology as a valuable educational tool in ODeL institutions, helping students deepen their understanding of subject matter. Moreover, students exposed to technology-integrated modules were more likely to adopt technology for independent learning.